Electronic Music Review Nº 4 - von Reichenbach, Fernando (1967)
Revista-Contenido: EMscope ( Tristram Cary) Superserialismus - Is There a Cure ? Symposium: Mixer and Level Controls ( Robert A. Moog) Introduction to Mixers and Level Controls ( James Seawright) Fundamental Concepts of Electronic Music Mixers (Gerald Shapiro) Fundamental Design of Electronic Music Mixers (Hugh Le Caine) Some Applications of Electrical Level Controls ( Federic Rzewski) A Photoresistor Mixer for Live Performance ( Fernando von Reichenbach) The Sound Level Photogrammer ( Robert A. Moog) Construction of a Simple Mixer ( Paul Ketoff) The Synket ( Kurt Stone, Joel Chadabe)